Grasslands may be more reliable carbon sinks than forests in California. (10th July 2018) - Dass, Pawlok; Houlton, Benjamin Z; Wang, Yingping; Warlind, David
Abstract: Although natural terrestrial ecosystems have sequestered ~25% of anthropogenic CO2 emissions, the long-term sustainability of this key ecosystem service is under question. Forests have traditionally been viewed as robust carbon (C) sinks; however, extreme heat-waves, drought and wildfire have increased tree mortality, particularly in widespread semi-arid regions, which account for ~41% of Earth's land surface. Using a set of modeling experiments, we show that California grasslands are a more resilient C sink than forests in response to 21st century changes in climate, with implications for designing climate-smart Cap and Trade offset policies. The resilience of grasslands to rising temperatures, drought and fire, coupled with the preferential banking of C to belowground sinks, helps to preserve sequestered terrestrial C and prevent it from re-entering the atmosphere. In contrast, California forests appear unable to cope with unmitigated global changes in the climate, switching from substantial C sinks to C sources by at least the mid-21st century. These results highlight the inherent risk of relying on forest C offsets in the absence of management interventions to avoid substantial fire-driven C emissions. On the other hand, since grassland environments, including tree-sparse rangelands, appear more capable of maintaining C sinks in 21st century, such ecosystems should be considered as an alternative C offset to climate-vulnerable forests. The further development of climate-smart approaches in California's carbon marketplace could serve as an example to offset programs around the world, particularly those expanding into widespread arid and semi-arid regions.